Legal Policy on Worker Protection in Labor-Intensive Industries: an Analytical Framework Based on the Values of the Pancasila Rule of Law - Andry Effendy; Henry Wardana Tirtawiguna (Publikasi Indonesia, 2026)
The labor-intensive industry plays a strategic role in Indonesia’s national development as a major source of employment, a driver of the manufacturing sector, and a significant contributor to economic growth. Previous studies have primarily focused on labor law reforms or specific aspects of worker protection, without providing a comprehensive normative analytical framework that integrates the values of the Pancasila-based rule of law as parameters for evaluating the direction of labor legal politics in labor-intensive industries. This study aimed to analyze the development of labor legal politics in labor-intensive industries, evaluate its direction based on Constitutional Court Decision Number 91/PUU-XVIII/2020 and Constitutional Court Decision Number 168/PUU-XXI/2023, and formulate a reconstruction of labor legal politics through the Pancasila Legal Politics Analysis Framework (KAPHP) as a normative analytical model. This research employed normative legal research using statutory, conceptual, historical, and case approaches. Primary legal materials consisted of the 1945 Constitution of the Republic of Indonesia, labor legislation, and Constitutional Court decisions, which were analyzed alongside secondary legal materials through qualitative and prescriptive analysis. The findings revealed that Indonesia’s labor legal politics had evolved toward a constitutional balance paradigm that harmonized workers’ constitutional rights, legal certainty, industrial sustainability, and economic development based on Pancasila values. Furthermore, this study proposed the Pancasila Legal Politics Analysis Framework (KAPHP) as a normative analytical model synthesized from the principles of legal politics, the Pancasila rule of law, the welfare state concept, and the constitutional protection of workers’ rights.